Migration of local earthquakes in the gulf of aqaba, north red sea (2012)
ABSTRACTThe Gulf of Aqabah has been considered one of the most seismically-active regions in the Middle East during the last 15 years; a catalogue of 1,415 earthquakes (duration magnitude Md and gt; 2. 8) during 19851995, compiled by Al-Arifi (1996) and Al-Shaabi (1998), mainly based on data from King Saud University. Seismic Studies Center (SSC), Saudi Arabia, for 28°- 30°N and 30°-36°E, has been used for studying local aftershock migration . Aftershocks migrated northwards about 60 km for the 1993 sequence and about 70 km for the 1995 sequence and also to shallow focal depths (15 km focal depth for 1993 main-shock) . Depths reduced as time elapsed until reaching 2 km for the last strong aftershock (Md=5 . 2) which occurred during the late stage of the sequence . The 1993 main-shock caused a redistribution of stresses to the parallel faults' segment where the largest 1993 aftershock occurred triggering these faults' segment to become an area of stress nucleation and generated the 1995 main-shockRESUMENEl Golfo de Aqabah ha sido considerada una de las regiones con más actividad sísmica del Medio Oriente durante los últimos 15 años . Un catalogo de 1415 terremotos (magnitud de duración Md and gt;2. 8) entre 1985-1995, compilado por Al-Arifi (1996) y Al-Shaabi (1998), basado principalmente en datos de la Universidad King Saud, Centro de Estudios Sísmicos (SSC), Arabia Saudita, para la zona ubicada entre 28°- 30°N y 30°-36°E, ha sido usado para estudiar la migración de replicas locales Las replicas migraron unos 60 km al norte para la secuencia correspondiente al año 1993 y unos 70 km para la secuencia por el año 1995 y también hacia bajas profundidades focales (15km de profundidad focal para el evento principal en el año 1993) . Las profundidades se redujeron con el tiempo hasta alcanzar 2 km para la ultima replica fuerte (Md=5 2) que ocurrió durante la última etapa de la secuencia El principal evento del año 1993 causo una redistribución de los esfuerzos hacia el segmento de las fallas paralelas donde la mayor replica en el año 1993 ocurrió, desencadenando el movimiento de estas fallas para llegar a ser un área de nucleación y generando el principal evento en el año 1995